PERLINDUNGAN HUKUM TERHADAP PEKERJA/BURUH DALAM PERJANJIAN KERJA WAKTU TERTENTU (PKWT) DITINJAU DARI UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Fajrin Pane, Muhammad (MEDIA HUKUM, 2014)
There are subdivisions of workers between the laborers in certain time and the workers in uncertain time started from the job in certain time in jobs exercises. Related to those cases, so the problems that have been discussed in this legislations with the laborers in certain tinme of job contract in regulations of legislations and the legal protections for the laborers who connected with PKWT.